2016
DOI: 10.1016/j.jmbbm.2016.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Cell elasticity with altered cytoskeletal architectures across multiple cell types

Abstract: The cytoskeleton is primarily responsible for providing structural support, localization and transport of organelles, and intracellular trafficking. The structural support is supplied by actin filaments, microtubules, and intermediate filaments, which contribute to overall cell elasticity to varying degrees. We evaluate cell elasticity in five different cell types with drug-induced cytoskeletal derangements to probe how actin filaments and microtubules contribute to cell elasticity and whether it is conserved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
110
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(120 citation statements)
references
References 61 publications
9
110
1
Order By: Relevance
“…Similarly, the local contribution of actin in intracellular rheology can be investigated in detail using our method, as best illustrated by the differences we observed between the effects of two actin-destabilizing drugs, LatA and CytoD. Although actin destabilization is mostly thought to soften the cell interior, its precise effect on intracellular mechanics is still not clear (44) and probably depends on the cell type (61). Surprisingly, although in LatA-treated cells the shear modulus dropped and bead diffusion was facilitated, we did not detect any effect upon treatment with CytoD (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, the local contribution of actin in intracellular rheology can be investigated in detail using our method, as best illustrated by the differences we observed between the effects of two actin-destabilizing drugs, LatA and CytoD. Although actin destabilization is mostly thought to soften the cell interior, its precise effect on intracellular mechanics is still not clear (44) and probably depends on the cell type (61). Surprisingly, although in LatA-treated cells the shear modulus dropped and bead diffusion was facilitated, we did not detect any effect upon treatment with CytoD (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…We found that the mobility of QDs within fibroblasts was less affected by nocodazole treatment than cytochalasin D treatement, which is consistent with prior studies showing that the mechanical properties of fibroblasts do not change significantly when exposed to nocodazole. 2 From the particle tracks, MSD was determined using MATLAB 43 . MSDs for QDs within fibroblasts, fibrosarcoma cells, and cytochalasin D treated fibroblasts are shown in Figure 1d–f respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A contributor to this confinement is the cytoskeleton itself, which features a mesh-like network with open spaces that direct the diffusion of macromolecules. The structural role of the actin and microtubule network within cell mechanics has been previously investigated 2–4 and together with the whole cytoskeleton network, cytoplasmic organelles, and molecular crowding, serves as obstacles to non-directed intracellular motion. Intracellular particle diffusion has become increasingly important within nanomedicine, where nano-scale photodynamic therapies 5–7 and gene or drug delivery systems 8–11 have made significant advances in disease treatment options.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the large sensor area in rheology systems results in a poor spatial resolution, on the order of centimeters. To address this, researchers turned to Atomic Force Microscopy (AFM) [3][4][5]. However, destructive sample preparation is required, preventing further imaging and molecular analysis.…”
Section: Introductionmentioning
confidence: 99%